Effects of supplementing fermented water hyacinth (Eichhornia crassipes) meal in hy-Line brown hens on oviduct morphometric characteristics, internal egg quality and shelf life - Nhara, Rumbidzai Blessing; Chikanga, Takudzwa Josh; Baloyi, Joseph Jimu; Antonio, Joe (Frontiers in Animal Science, 2026)
The study investigated the effects of partially replacing soybean meal with fermented water hyacinth meal (FWHM) on oviduct morphometry and egg quality in Hy-Line hens. Ninety-six eighteen-week-old hens were randomly assigned to one of three dietary treatments: 0% (Control), 2.5%, or 5% FWHM. Following a 2-week dietary adaption period, hens were fed the experimental diets for twelve weeks. Internal egg quality, and eggshell traits were measured at regular intervals during the feeding trial, with freshly laid eggs stored at 4°C (39.2°F) under approximately 70-80% relative humidity and equilibrated at room temperature (21-25°C) for one hour prior to analysis to minimize condensation and thermal shock effects. Oviduct morphometric measurements were obtained at the end of the study, to evaluate dietary effects. Most oviduct morphometric parameters were unaffected by FWHM supplementation (P > 0.05). Notable exceptions were higher infundibulum weight in the 5% FWHM group (1.65 ± 0.46 g) compared to the 2.5% group (1.10 + 0.34 g; P < 0.05), and lower magnum weight in the 5% FWHM group (27.84 ± 7.24 g) relative to Control (38.28 ± 7.01 g; P < 0.05). Internal egg quality and eggshell characteristic traits: yolk and albumen weights, Haugh unit and eggshell thickness were largely unchanged. Yolk pH was lower in the 2.5% (6.63 ± 0.09) and 5% (6.60 ± 0.10) FWHM groups versus Control (6.70 ± 0.13; P < 0.05), while yolk diameter slightly decreased in FWHM-fed hens. These findings indicate that FWHM can be included in laying hen diets at levels up to 5% without adversely effecting reproductive tract development or core egg quality, while modulating yolk traits that may enhance egg shelf life.